2022
DOI: 10.48550/arxiv.2203.14671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Markovian thermal operations boosting the performance of quantum heat engines

K. Ptaszyński

Abstract: It is investigated whether non-Markovianity, i.e., the memory effects resulting from the coupling of the system to its environment, can be beneficial for the performance of quantum heat engines. Specifically, two physical models are considered. The first one is a well known single-qubit Otto engine; the non-Markovian behaviour is there implemented by replacing standard thermalization strokes with so-called extremal thermal operations which cannot be realized without the memory effects. The second one is a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, there are several studies [57][58][59][60] that showed that non-Markovian effect is actually beneficial for enhancing the performance even in the regime of weak coupling [46,57]. Although there are some objections [61][62][63] to this non-Markovian boosting due to the neglecting of the coupling and decoupling cost, recently genuine non-Markovian advantage has been reported [64] taking into account these previous shortcomings. Evidently, it is an intriguing task to investigate the interplay between strong interaction and non-Markovianity [65] with respect to thermodynamic tasks, and it still remains a largely unexplored area.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are several studies [57][58][59][60] that showed that non-Markovian effect is actually beneficial for enhancing the performance even in the regime of weak coupling [46,57]. Although there are some objections [61][62][63] to this non-Markovian boosting due to the neglecting of the coupling and decoupling cost, recently genuine non-Markovian advantage has been reported [64] taking into account these previous shortcomings. Evidently, it is an intriguing task to investigate the interplay between strong interaction and non-Markovianity [65] with respect to thermodynamic tasks, and it still remains a largely unexplored area.…”
Section: Introductionmentioning
confidence: 99%